The applicability of a weight loss grading system in cancer cachexia: a longitudinal analysis - Vagnildhaug, Ola Magne; Blum, David; Wilcock, Andrew; Fayers, Peter; Strasser, Florian; Baracos, Vickie E.; Hjermstad, Marianne J.; Kaasa, Stein; Laird, Barry; Solheim, Tora S. (Wiley, 2017)
Background